A New Centennial for Brazil and Its National Museum - Duarte, Luiz Fernando Dias (Anais do Museu Paulista: História e Cultura Material, 2022)
Brazil's Museu Nacional celebrated its second centennial in 2018, the same year it had most of its headquarters and collections destroyed by a fire. The date preceded by four years the commemoration of the second centennial of the country's independence, when it was to join prominently the general reflection and the festivities prompted by the event. In the context of the restoration of the Palace of São Cristóvão and the general reconstitution of the institution, intense work was required to reassess the meaning of its traditional "national" character and its responsibility as the oldest museum in the country, leading to an awareness of the changes in the general national social and cultural framework, particularly for a museum of “natural history" and anthropology. The process of discussing new facilities, collections, and future exhibitions is a strategic process in this reevaluation - with lasting implications for the institution's service to the nation.